Government NGO relationship in Africa,Asia,Europe and MENA - Marchetti,Raffaele,Ed (Routledge, 2019)
This volume brings together some of the most recent scholarship on government and civil society. It examines the axis of the relationship between national governments and civil society organisations (NGOs) by highlighting commonalities as well as differences among four key regions in the world. Using the stability vs. instability framework, the book explores a range of pertinent issues, including human rights, development, foreign policy, state-building, regime change, governance frameworks, wars and civil liberties. It studies diverse situations, from those entailing comprehensive cooperation to those involving politically contentious and revolutionary activities.